2018
DOI: 10.1177/0363546518782975
|View full text |Cite
|
Sign up to set email alerts
|

Integrity of the Untorn Articular-Sided Tendon in Bursal-Sided Partial-Thickness Rotator Cuff Tear: A Comparative Study of Apoptotic Activity in Torn and Untorn Layers

Abstract: The untorn articular layer of PTRCTs is abnormal, which triggers postoperative pain and further rotator cuff tears. Therefore, treatment of the abnormal untorn articular layer is essential in bursal-sided PTRCTs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…A recent comparative study of apoptotic activity in torn and untorn layers demonstrated that apoptotic gene expression is increased not only in the torn bursal layer but also in the untorn articular layer of PTRCT. 46 Because the untorn articular layer of PTRCT is abnormal, which triggers postoperative pain and further rotator cuff tears, Yang et al 46 recommended that treatment of the abnormal untorn articular layer is essential in bursal side PTRCT. Compared with the bursal side tears, apoptotic gene expression might be further increased in both-sided PTRCT, and also, these tears have abnormal both-sided tears.…”
Section: Discussionmentioning
confidence: 99%
“…A recent comparative study of apoptotic activity in torn and untorn layers demonstrated that apoptotic gene expression is increased not only in the torn bursal layer but also in the untorn articular layer of PTRCT. 46 Because the untorn articular layer of PTRCT is abnormal, which triggers postoperative pain and further rotator cuff tears, Yang et al 46 recommended that treatment of the abnormal untorn articular layer is essential in bursal side PTRCT. Compared with the bursal side tears, apoptotic gene expression might be further increased in both-sided PTRCT, and also, these tears have abnormal both-sided tears.…”
Section: Discussionmentioning
confidence: 99%
“…The histological method was used to detect the pathologic changes of subcutaneous tumors and performed as described previously [25]. Brie y, mice from normal diet group and ketogenic diets group were euthanized by CO 2 inhalation on day 30 after ketogenic diets or normal diets.…”
Section: Histopathological Examination Of Tumormentioning
confidence: 99%
“…In this study, three kinds of non-specific histological staining techniques were performed on the Achilles tendon tissues: hematoxylin-eosin (HE) staining, Safranin O/ fast green (SOFG; fast green and Safranin) staining, and Masson's trichrome staining (Wuhan Servicebio Technology Co., Ltd., China). According to the conventional protocols (24)(25)(26), the prepared tissue sections were stained with the corresponding staining solutions and photomicrographs were obtained. In order to review the Masson's staining, Image-Pro Plus 6.0 software (Media Cybernetics, Silver Spring, USA) was applied to analyze the proportions of fresh and immature collagen fibers within the Achilles tendon tissues.…”
Section: Histological Stainingmentioning
confidence: 99%